rancang RANCANG BANGUN PROTOTYPE ALAT PENGUKUR JARAK VERTIKAL DAN HORIZONTAL BERBASIS INFRARED DAN RODA - Safwan Safwan; Ika Mawaddah; Zakwansyah (J-Innovation, 2021)
Currently there are several tools that can be used for the process of measuring vertical and horizontal distances in one tool, but the process of use is still difficult for the layman to use. The main objective of this final project is to design vertical and horizontal measurement tools with 2 sensors for the horizontal and vertical measurement process into 1 tool only to make it easier for the layman to use as well. This tool is equipped with Incremental rotary encoder as horizontal distance meter, Infrared sensor as vertical distance meter, and seven segment as measurement data viewer by Incremental rotary encoder and Infrared in centimeter(cm)